Metabolic Characteristics of Advanced Biliary Tract Cancer Using (18)F-Fluorodeoxyglucose Positron Emission Tomography and Their Clinical Implications - Cho, Kyoung-Min (Oncologist, 2015)
BACKGROUND. In advanced biliary tract cancer (BTC), the metabolic landscape has not been evaluated by (18)F-fluorodeoxyglucose (FDG) positron emission tomography (PET) yet. Furthermore, reports of the clinical implications of these metabolic features are limited. We aimed to evaluate the metabolic features and their clinical relevance in advanced BTC using (18)F-FDG PET. PATIENTS AND METHODS. We consecutively enrolled patients with advanced BTC who underwent (18)F-FDG PET prior to palliative chemotherapy between 2003 and 2013. We evaluated the findings of PET, such as SUV(max), the number of lesions and organs with FDG uptake, pathologic findings, and clinical outcomes. RESULTS. A total of 106 patients were enrolled: (53 intrahepatic cholangiocarcinoma [ICC], 7 extrahepatic BTC, 30 gallbladder cancer [GB Ca], and 16 ampulla of Vater cancer [AoV Ca]). The median SUV(max) differed according to the primary origin (ICC, 9.10; extrahepatic BTC, 5.90; GB Ca, 9.10; and AoV Ca, 6.37; p = .008) and histologic differentiation (well differentiated, 4.95; moderately differentiated, 6.60; poorly differentiated, 14.50; p = .004). Patients in the high metabolic group (SUV(max) of ≥7.5) had more poorly differentiated histology and more organs and lesions with FDG uptake than did those in the low metabolic group (SUV(max) of <7.5). The low metabolic group had a significantly longer OS (11.4 vs. 7.4 months, p = .007) and PFS (6.6 vs. 4.3 months, p = .024) than high metabolic group. In multivariate analysis, SUV(max) was a significant prognostic factor for overall survival (OS; p = .047) and progression-free survival (PFS; p = .039). CONCLUSION. Metabolic characteristics of advanced BTC differ according to primary origin and histology. These metabolic features could be prognostic factors for OS and PFS in advanced BTC. IMPLICATIONS FOR PRACTICE: The metabolic landscape of advanced biliary tract cancer and its clinical meanings have not yet been comprehensively studied. This study shows that metabolic characteristics of advanced biliary tract cancer differ significantly according to primary origin and histology. Moreover, this metabolic activity is associated with patients’ outcomes, including overall survival and progression-free survival. This study supports tumor heterogeneity in terms of cancer metabolism in biliary tract cancer.